Biomarkers in early-stage colorectal cancer: ready for prime time? - Church, D; Midgley, R; Kerr, D (2012)
BACKGROUND/AIMS: During the last two decades, hundreds of reports have detailed putative prognostic and predictive biomarkers for colorectal cancer (CRC). However, the majority of these studies have been small and retrospective, reporting results that are highly likely to represent false positives. Consequently, their relevance to clinical practice requires definition. METHODS: Review of published literature on CRC biomarkers, focusing on early-stage disease. RESULTS: Although most putative biomarkers have failed to be validated in subsequent studies, level I evidence now indicates that tumour microsatellite instability can be used to identify a cohort of patients with stage IIA disease at low risk of relapse who can be spared adjuvant chemotherapy. Emerging data suggest that gene expression arrays may have a role in selecting patients with stage IIA disease and mismatch repair-proficient tumours for chemotherapy following tumour resection. CONCLUSION: Despite the profusion of biomarker literature, only mismatch repair status can be recommended as routine in current clinical practice. High-quality, adequately powered studies are essential to accurately define the utility of existing and putative biomarkers, and to support their rational application in the clinic.